Multidisciplinary Approach of Neonatal Intensive Care in Bam Syndrome: A Rare Case Report - Putri Humaira, Tabina; Tresna, Queen Choirunisa Tansa Tresna; Nugrohoputri, Tsabita Aurelia; Apsari, Luisa Ziesta Dian; Fatoni, Syifa Annisa; Wibowo, Tunjung (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2024)
Bosma Arhinia Microphthalmia Syndrome (BAMS) is a very rare condition characterized by eye defects, a complete absence of nose, and hypogonadotropic hypogonadism, which is caused by a genetic mutation in the gene SMCHD1 located in chromosome 18p11. Fewer than 100 cases were reported globally over the previous century, and only a few clinical studies have discussed its occurrence and management in Indonesia. Therefore, there are no clear guidelines about the management of neonates with BAMS due to its rarity. This study reported a BAMS neonatal patient with atresia choana, microphthalmia, pectus excavatum, facial dysmorphic, unspecified hearing loss, and hydronephrosis. An MSCT scan of the patient revealed an absence of cavum nasi, undeveloped paranasal sinus, microcephaly, abnormal size of bulbus oculi sinistra, and the presence of cleft palate. This condition prompted the patient to require intensive medical support early in life due to breathing and feeding difficulties, as well as the need for several examinations on many aspects to determine the extent of the syndrome which has different characteristics for each individual. Therefore, a multidisciplinary approach is necessary to provide the most suitable management for each neonate with BAMS. This case report described the patient’s neonatal intensive care and management with a multidisciplinary team which includes a neonatologist, an ophthalmologist, an otorhinolaryngologist, a radiologist, an endocrinologist, and an oral and maxillofacial surgeon. This study aims to improve the knowledge of BAMS patient management in the future since there are no standardized guidelines or treatment protocols, and the case is rarely studied.